Peningkatan Keterampilan Berbicara Melalui Metode Time Token Arends Pada Siswa Kelas V SDN 132 Babalohe Kabupaten Bulukumba - Sasmitha Sasmitha; Aliem Bahri; Muhammad Saeful (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The aim of this research is to improve speaking skills through the Time token areinds method in class V Indonesian language subjects at SDN 132 Babalohe. The type of research used is pre-experimental research with the aim of. The research design used was a one-shot case study, namely an experimental research carried out to show the strength of measurement and scientific value of a research design and the experimental units in this research were 19 students in class V at SDN 132 Babalohe as a trial class for implementing the use of Time. Arends Token. The data collection technique in this research was carried out using a student interest in learning questionnaire sheet technique (student responses). The research results show that analysis of student interest in learning questionnaire data shows that the ideal score of 92.89% is in the very good category, because it is in the range of 75% - 100%,Keywords: Effectiveness of Bolding Media (Rolling Ball), Short Story Writing Skills